Vulnerability to food insecurity in rural Punjab, Pakistan. Issue 9 (31st July 2018) - Bashir, Muhammad Khalid; Schilizzi, Steven; Sadler, Rohan; Ali, Ghaffar
Abstract : Purpose: The purpose of this paper is to measure the vulnerability to food insecurity in rural Punjab, Pakistan. Design/methodology/approach: Primary data of 1, 152 households were collected. The extent of food deficiency was measured using dietary intake assessment method (seven days). Value at Risk (VaR) and conditional Value at Risk (cVaR), a method widely used for risk analysis in financial institutes, were applied to assess the vulnerability to food insecurity. Findings: In total, 23 percent of the sample households were measured as food deficient. The VaR and cVaR results identified that the lowest 3 percentiles (up to 30 percent) were at risk to become food deficient without any seasonal shortages. In case of shocks, up till sixth percentiles (60 percent) will be as at risk of food deficiency. This study suggests that multi-period data, at least quarterly, are required to predict vulnerability. It is suggested that a blanket policy is not a good approach. Once the most vulnerable households are identified, a targeted approach must be opted. Originality/value: Generalizing the results of one week's calorie calculations may produce biased results that may mislead the policy process. A multi-period data collection is costly and cumbersome. The application of VaR and cVaR helps overcome this issue. Furthermore, this is one of the initial studies to apply these methods to food security analysis.